Isolasi Senyawa Bioaktif Antibakteri Pada Ekstrak Etanol Teripang Pasir (Holothuria scabra) di Kepulauan Selayar - Yuliana Yuliana; Asriani Ilyas; Suriani Suriani (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2017)
Abstract: Sand sea cucumber (Holothuria scabra) is one type of marine invertebrates with family Holothuriidae and is a member of Enchinodermata animals. Types of animals have been used as raw materials in traditional medicine. The aims of this reseach are to isolate the bioactive compounds contained in the ethanol extract of sand sea cucumbers and to know its major bioactivity. This research conducted in several methods namely extraction, fractionation, identification using thin layer chromatography (TLC) and qualitative test to determine secondary metabolites, as well as the characterization by FTIR. Results obtained from the isolation is a pure isolate by weight of 0.0203 grams of yellowish white paste. Purification was performed using three systems eluent as well as FTIR spectroscopy. The results showed that the compounds in pure isolates are alkaloids. Viscous extract and pure isolates subsequently tested its antibacterial test disc diffusion method using bacteria Salmonella thypi and Staphylococcus aureus. The results showed that the extract activity of the bacteria Salmonella thypi and Staphylococcus aureus into the strong category with optimum diameter of clear zone respectively 11.50 mm and 12.30 mm. Keyword: Bioaktive Compound, Disc Diffusion, Isolation, Sand Sea Cucumber (Holothuria scabra).